Designing Product Development Contracts in the Presence of Managerial Lobbying - Bao, Ying; Shi, Mengze; Kalra, Ajay (Management Science, 2022)
We examine a firm’s contract design problem in the context of allocating resources to new products with uncertain potential being developed by the managers vying for funds. The firm faces twin problems of identifying the right project(s) to prioritize them, and next also motivate the managers to exert effort in implementing the project to successful fruition. The firm’s contract design can incentivize the managers either using a resource-based incentive plan, which offers a reward based on the number of resources invested in the projects, or offering a resource-decoupled incentive plan, which provides a standard reward disregarding the differential amount of resources invested. We consider a set-up where the manager has private information about project quality. During the prioritizing first stage, we allow the manager to lobby for the project by manipulating the signal of the project quality. We show that a resource-decoupled incentive plan impacts the lobbying by encouraging the manager of the higher quality project to manipulate the quality signal more to stand out. Therefore, although a resource-based incentive plan is more efficient in inducing the manager in exerting implementation effort, a resource-decoupled incentive plan may be preferred as it leads to more accurate resource allocation. Thus, allowing lobbying that involves exaggeration may be beneficial by amplifying a firm’s ability to identify high caliber projects. We demonstrate the robustness of our results in models where the firm chooses the level of evaluation threshold, where there are multiple projects, and where the project evaluations involve a ranking procedure. This paper was accepted by Duncan Simester, marketing.